Analyzing formation of silver nanoparticles from the filamentous fungus Fusarium oxysporum and their antimicrobial activity - AHMED, Abd-Almohaimen (Turk J Biol, 2018)
In recent years much attention has been paid to the biosynthesis of silver nanoparticles (AgNPs) and their important medical applications. The current study employs Fusarium oxysporum for the formation of silver nanoparticles and examines the antimicrobial activity of the particles against some multidrug-resistant (MDR) microbes. Silver nitrate was transformed into silver oxide, forming well-dispersed nanoparticles, by the action of F. oxysporum metabolically. The size of the nanoparticles ranged from 21.3 to 37.3 nm, and UV-spectroscopy showed a peak at 408-411 nm. Moreover, SEM, TEM, and AFM results revealed spherical and oval shapes and showed no sign of aggregation. Furthermore, the FT-IR histogram detected amide I and amide II, which are responsible for the stability of AgNPs in the aqueous solution. The AgNPs halted the growth of MDR bacteria, including some members of Enterobacteriaceae and Staphylococcus species at a concentration of 50% (v/v). The AgNPs also have the ability to inhibit pathogenic yeasts Candida albicans and Candida krusei. The AgNPs displayed antigrowth activity against MDR microbes, suggesting that they might be potential alternatives to antibiotics. However, additional studies may be necessary to substantiate the fact that the benefits of using nanoparticles outweigh the potential risks.